2022
DOI: 10.1093/ntr/ntac057
|View full text |Cite
|
Sign up to set email alerts
|

Why Smoke Flavor Capsule Cigarettes? Preferences and Perceptions Among Adult Smokers in Mexico

Abstract: Purpose Flavor capsule cigarettes are rapidly gaining global market share, particularly in Latin America. This paper compares profiles and perceptions of smokers who prefer flavor capsule cigarettes and those who do not in Mexico. Methods We analyzed data from six online surveys of adult Mexican smokers (n=4488) from 2018-2020. Participants identified their preferred brand variety characteristics (no capsule; one capsule; two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…To optimize the potential impact of legalizing ENDS, their regulation should be viewed as a component of a comprehensive strategy alongside strong tobacco control policies and enforcement to steer consumers away from cigarette smoking. Specifically, regulations should ban flavor capsule cigarettes, which come in a range of flavors as ENDS and are particularly popular among youth, women, and nondaily smokers (64), with increasing use rates (65,80). It is also imperative for Mexico to ratify and enforce the Protocol to Eliminate Illicit Tobacco Products (71,72], as its enforcement would play a pivotal role in curbing access to and availability of tobacco and nicotine products that pose potential harm to public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To optimize the potential impact of legalizing ENDS, their regulation should be viewed as a component of a comprehensive strategy alongside strong tobacco control policies and enforcement to steer consumers away from cigarette smoking. Specifically, regulations should ban flavor capsule cigarettes, which come in a range of flavors as ENDS and are particularly popular among youth, women, and nondaily smokers (64), with increasing use rates (65,80). It is also imperative for Mexico to ratify and enforce the Protocol to Eliminate Illicit Tobacco Products (71,72], as its enforcement would play a pivotal role in curbing access to and availability of tobacco and nicotine products that pose potential harm to public health.…”
Section: Discussionmentioning
confidence: 99%
“…These rates are applied each year. We conduct a sensitivity analysis and consider switching rates at 25% from US PATH rates to reflect the uncertainty on switching from cigarettes to ENDS when permissive cigarette regulations are in place (e.g., legalization of flavored tobacco-products) (64, 65). We also consider 75% of those switching rates from PATH to showcase a scenario where strong cigarette policies and strong enforcement are in place.…”
Section: Methodsmentioning
confidence: 99%
“…Flavour capsule cigarettes (FCCs) contain one or two capsules in the cigarette filter which release flavour when the consumer crushes it 2. They come in several flavours, including both traditional flavours (eg, menthol, berry) and those with ‘concept descriptors’ (eg, Mykonos Nightfall) 3–5. The choice of flavours, the enjoyment of clicking the capsule and the ability to customise when and if to crush the capsule contribute to their appeal 6–8.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these trends, there is a dearth of research on the prevalence of FCC use in countries where these products are available on the market 18. Prevalence data (current or ever use among people who smoke) exist for only a handful of countries, including Australia,19 Chile,20 Mexico,5 19 21 22 Republic of Korea,23 the UK24 and the USA 19 25 26. Previous studies have found that FCC appeal and use is associated with younger age,5 19–21 24 and in some countries, with being female 5 19–21 23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation